2023
DOI: 10.3390/recycling8010012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Mechanical Recycling Behaviour of Amorphous and Semicrystalline Polymers: A Case Study

Abstract: The increase in waste has motivated the adoption of the circular economy concept, which assumes particular relevance in the case of plastic materials. This has led to research of new possibilities for recycling plastics after their end-of-life. To achieve this goal, it is fundamental to understand how the materials’ properties change after recycling. This study aims to evaluate the thermal and mechanical properties of recycled plastics, namely polycarbonate (PC), polystyrene (PS), glass fibre-reinforced polyam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Fibers chains breaking after reprocessing operations (recycling cycles) causes the fall of the molecular weight of the polymer and eases the flow of the materials, which leads to a high MFI. Similar results were revealed by Costa et al,20 who reported that the melt flow rate (MFR) of PA6-GF30 are significantly increased after recycling. Figure3Bshows that the MFI decreased with the substitution of 50 wt% of the recycled PA6/GF30 composites (N1 or N2) with 50 wt% of the virgin PA6/GF30 composite (N0).…”
supporting
confidence: 89%
See 4 more Smart Citations
“…Fibers chains breaking after reprocessing operations (recycling cycles) causes the fall of the molecular weight of the polymer and eases the flow of the materials, which leads to a high MFI. Similar results were revealed by Costa et al,20 who reported that the melt flow rate (MFR) of PA6-GF30 are significantly increased after recycling. Figure3Bshows that the MFI decreased with the substitution of 50 wt% of the recycled PA6/GF30 composites (N1 or N2) with 50 wt% of the virgin PA6/GF30 composite (N0).…”
supporting
confidence: 89%
“…[8][9][10][11] Mechanical recycling techniques start with cutting, grinding and reprocessing of wastes plastics generated after the end-of-life or during production to produce new component for a wide application. 12,13 Studies on recycling process and its effects on properties have been conducted for a large number of polymers such as polypropylene (PP), 14,15 high density polyethylene (HDPE), 16 low density polyethylene (LDPE), 16,17 polyethylene terephthalate (PET), [18][19][20] polystyrene (PS), [20][21][22] polycarbonate (PC), 20,23 and polyamide 6 (PA6). 20,24,25 PA6 is a semicrystalline thermoplastic polymer that finds extensive use in various engineering applications, especially in the electronic and automobile industries due to its good mechanical properties and ease of processing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations